Purkinje Cell Compartmentation in the Cerebellum of the Lysosomal Acid Phosphatase 2 Mutant Mouse (Nax - Naked-Ataxia Mutant Mouse) - Bailey, Karen (Public Library of Science, 2014)
The Acp2 gene encodes the beta subunit of lysosomal acid phosphatase, which is an isoenzyme that hydrolyzes orthophosphoric monoesters. In mice, a spontaneous mutation in Acp2 results in severe cerebellar defects. These include a reduced size, abnormal lobulation, and an apparent anterior cerebellar disorder with an absent or hypoplastic vermis. Based on differential gene expression in the cerebellum, the mouse cerebellar cortex can normally be compartmentalized anteroposteriorly into four transverse zones and mediolaterally into parasagittal stripes. In this study, immunohistochemistry was performed using various Purkinje cell compartmentation markers to examine their expression patterns in the Acp2 mutant. Despite the abnormal lobulation and anterior cerebellar defects, zebrin II and PLCβ4 showed similar expression patterns in the nax mutant and wild type cerebellum. However, fewer stripes were found in the anterior zone of the nax mutant, which could be due to a lack of Purkinje cells or altered expression of the stripe markers. HSP25 expression was uniform in the central zone of the nax mutant cerebellum at around postnatal day (P) 18–19, suggesting that HSP25 immunonegative Purkinje cells are absent or delayed in stripe pattern expression compared to the wild type. HSP25 expression became heterogeneous around P22–23, with twice the number of parasagittal stripes in the nax mutant compared to the wild type. Aside from reduced size and cortical disorganization, both the posterior zone and nodular zone in the nax mutant appeared less abnormal than the rest of the cerebellum. From these results, it is evident that the anterior zone of the nax mutant cerebellum is the most severely affected, and this extends beyond the primary fissure into the rostral central zone/vermis. This suggests that ACP2 has critical roles in the development of the anterior cerebellum and it may regulate anterior and central zone compartmentation.